Perancangan UI/UX Di Dalam Aplikasi Open Sport Menggunakan Metode Design Thinking - Andrian Doni Saputra; Bayu Prasetyo; Octa Selsa Is Anggraini; Nadia Putri; Ina Sholihah Widiati (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2023)
In a modern era like this, it is important for field rental businesses to move towards digital marketing so that they can survive and develop in a time when the need for the internet in everyday life is very high. And for that the author makes an online field reservation application and a field reservation application as an intermediary between users and business people. The purpose of this application is to design a field ordering application that can be easily and quickly accessed by customers via gadgets, so that this application can later be accepted by users from all walks of life (Saktiadji et al., 2023). And this application also provides cash and non-cash payments depending on the user, the system in this application can also make reservations in advance without coming directly to the field you want to rent. Everything can be done just by going through this application and you don't need to move from your place. With the existing system in this application, it is expected to increase the attractiveness and convenience of application users. And this application is also an alternative to additional income for sports field rental businesses.